Optical and relaxometric properties of monometallic (EuIII, TbIII, GdIII) and heterobimetallic (ReI/GdIII) systems based on a functionalized bipyridine-containing acyclic ligand. Issue 20 (25th April 2016) - Leygue, Nadine; Boulay, Alexandre; Galaup, Chantal; Benoist, Eric; Laurent, Sophie; Vander Elst, Luce; Mestre-Voegtlé, Béatrice; Picard, Claude
Abstract : The photophysical and relaxometric properties, in aqueous solution, of Ln-BPMNTA complexes and a derived Re I /Gd III dinuclear complex are reported in this paper. Abstract : A series of lanthanide complexes of [LnL(H2 O)] 2− composition where Ln = Eu III, Tb III or Gd III has been studied for determining their photophysical and relaxometric properties in aqueous solution. The bifunctional ligand L (H5 BPMNTA) is an acyclic chelator based on a central functionalized 2, 2′-bipyridine core and two iminodiacetate coordinating arms. The mono-aqua Eu III and Tb III complexes display attractive spectroscopic properties with an excitation wavelength at 316 nm, similar excited state lifetimes and overall quantum yields (in the ranges 0.5–0.6 ms and 10–13%, respectively) in Tris buffer (pH 7.4). The proton longitudinal relaxivity, r 1, of the Gd III complex is 4.4 mM −1 s −1 at 20 MHz and 310 K, which is comparable to that of the clinically used Gd-DTPA (Magnevist®). Interestingly, the water exchange rate between the coordination site and the bulk solvent is very fast ( K ex = 2.6 × 10 8 s −1 at 310 K). The ability of the complex to bind non-covalently to human serum albumin (HSA) was also examined by relaxometric measurements. We also report the synthesis and properties of a bimetallic complex based on Gd-BPMNTA and Re I (bpy)(CO)3 components. In this system, the Re core exhibits interesting photophysical properties ( λ em = 588 nm, Φ = 1.4%) and the Gd-BPMNTA core displays improved relaxivity ( r 1 = 6.6 mM −1 s −1 at 20 MHz and 310 K), due to an increase of the rotational correlation time. Besides these appealing optical and relaxometric properties, the presence of a reactive function on the structure proposes this potential dual imaging probe for conjugation to biomolecules or nanomaterials.